Expression of socio-cultural values in Javanese-Australian families: A study of code mixing and code switching - Ardi Setyawardana; St. Nurbaya (Universitas Negeri Yogyakarta, 2026)
This study examines the code-switching and code-mixing strategies of a Javanese-Australian diaspora family, namely the family behind the YouTube channel MyOzlife. Specifically, how code-switching and code-mixing function as a mechanism for maintaining the family's cultural identity in the digital space. This study uses a qualitative descriptive approach and, for analysis, employs Miles and Huberman's content analysis, grounded in the theory of social functions, to examine 65 speech events and present interpretive analysis of the code-switching and code-mixing patterns of Javanese-Indonesian families. On the other hand, further findings are in the form of integration with the theory of axiological values. The findings of this study indicate that the linguistic principles used by the family on the MyOzlife channel by 43.1% indicate personalization versus objectivation, so that the main meaning and motive of code-switching are the management of social distance and affective expression rather than referential needs. The findings of this study are in line with the sociolinguistic strategy of the Javanese-Australian MyOzlife family as a manifestation of the cultural axiological values ​​of rukun (social harmony), respect (hierarchy), and silaturahmi (family solidarity), which are manifested in using Javanese registers and religious interjections to transmit the values ​​of politeness norms that their multilingual generation wants to learn. These findings indicate that, in the context of this Javanese-Australian family, multilingual phenomena such as code switching and code-mixing are demonstrated as communicative competence strategies integrated into local and global identities.